Evaluation of immunochromatographic assay as a field test for the diagnosis of caprine brucellosis - TRANGADIA, B J; PRASAD, M C (The Indian Journal of Animal Sciences, 2018)
The present study was undertaken to assess the suitability of immunochromatographic assay (ICA) as a field test for the diagnosis of caprine brucellosis. Whole blood samples (570: 195 male goats, 375 female goats) were collected from selected organized herds and panjarapoles located in Southern Gujarat. Out of 570 animals tested, 19 (3.33%), 72 (12.63%) and 45 (7.89%) were positive by Rose Bengal plate test (RBPT), indirect ELISA (iELISA) and immunochromatographic assay (ICA) respectively. The sensitivity of RBPT and ICA vs iELISA was 26.39% and 61.11% respectively. Both the tests were 100% specific when compared with iELISA. Negative likelihood ratio for RBPT and ICA as compared to iELISA was 0.74 and 0.39 respectively. The negative predictive value for RBPT was 90.38% and 94.68% for ICA. However, the positive predictive values (PPV) for both the tests were 100%. McNemar chi-square test for independent data (with Yates’ correction) revealed significant difference in the positive proportion between RBPT vs iELISA as 9.30% and ICA vs iELISA as 4.91%. The concordance of iELISA with RBPT was moderate (k=0.385) while it was good (k=0.733) for ICA.